The Moral Implications of Human and Animal Vulnerability - Martin, Angela K. (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"Vulnerability has been an important topic in bioethical discourse over the last forty years. Its predominant focus was on human vulnerability but recently, animal vulnerability has become a topic of philosophical investigation as well. In this book, Angela K. Martin thoroughly addresses what animal vulnerability is, how and why it matters from a moral point of view, and how it compares to human vulnerability. She carefully explores both human and animal vulnerability, bringing out both their similarities and their difference, and she shows how vulnerability discourse can be made fruitful for animal ethics." -Nathan Nobis, Morehouse College, USA "This book offers one of the most comprehensive and helpful treatments of the concept of 'vulnerability' in applied ethics to date. In so doing, it offers a fresh perspective on our duties to non-human animals that will be of enormous benefit to bioethicists and animal ethicists alike." -Alasdair Cochrane, University of Sheffield, UK In this open access book, Angela K. Martin thoroughly addresses what human and animal vulnerability are, how and why they matter from a moral point of view, and how they compare to each other. By first defining universal and situational human vulnerability, Martin lays the groundwork for investigating whether sentient nonhuman animals can also qualify as vulnerable beings. She then takes a closer look at three different contexts of animal vulnerability: animals used as a source of food, animals used in research, and the fate of wild animals. Angela K. Martin is a Swiss National Science Foundation SNSF PRIMA-Grant Assistant Professor. She is based at the Philosophy Department of the University of Basel, Switzerland. .